Netherlands: 'Historic victory' as law amended to recognize that sex without consent is rape - Amnesty International (Amnesty International, 2023)
Responding to the news that the Netherlands’ House of Representatives has voted to amend the Sexual Offences Act by introducing a consent-based definition of rape.
Netherlands
Keywords: 2023-07 July